Quantification of Touch DNA on Glass, Plastic, and Ceramic Glasses - Novenalitha K. Sinukaban; I Ketut Junitha; Ni Nyoman Wirasiti; Ni Luh Suriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
In Indonesia, there are many criminal cases. Every criminal offender will certainly bring and leave something at the crime scene that can be used as a trial or evidence. In addition, perpetrators who accidentally or intentionally come into contact with surrounding objects can cause the transfer of trace evidence to these objects. DNA touch left on an object can provide information about the identity of individuals in contact with that object. This study aimed to determine the quantity and quality of DNA Touch in glasses made of glass, plastic, and ceramic that were touched by one proband and two probands. DNA extraction was carried out using the 5% Chelex method. using Univariate and one-way ANOVA. DNA quality was observed based on the comparison results of Å260 and Å280 on the SimpliNano spectrophotometer. The results showed that the concentration of DNA in glass, plastic and ceramics was not significantly different in each treatment. There was no interaction between the type of glass and hand touch, the average DNA concentration. Extracted DNA showed poor quality